Homeodomain-containing gene 10 inhibits cell apoptosis and promotes cell invasion and migration in osteosarcoma cell lines - Wen Xiong; Quan Zhou; Gang Liu; Xiang-Sheng Liu; Xin-Yu Li (Tumor Biology)
Homeodomain-containing gene 10 (HOXC10) belongs to the homeobox family, which encodes a highly conserved family of transcription factors that plays an important role in morphogenesis in all multicellular organisms. Altered expressions of HOXC10 have been reported in several malignancies. This study was aimed to reveal the expression profile of HOXC10 in osteosarcoma and evaluated whether HOXC10 is a molecular target for cancer therapy. We found that HOXC10 was up-regulated in osteosarcoma tissues compared with bone cyst specimens from The Cancer Genome Atlas database. Osteosarcoma MG63 cells were infected with HOXC10 shRNA expressing vector, and 143B cells were infected with HOXC10 expressing vector. We found that reduced expression of HOXC10 markedly impaired the ability of proliferation, invasion, and migration, and promoted cell apoptosis in vitro and in vivo. Up-regulated expression of HOXC10 promoted the proliferation, invasion, and migration, and inhibited apoptosis of 143B cells. Additionally, HOXC10 regulated apoptosis and migration via modulating expression of Bax/Bcl-2, caspase-3, MMP-2/MMP-9, and E-cadherin in both MG63 and 143B cells and in vivo. These results indicated that HOXC10 might be a diagnostic marker for osteosarcoma and could be a potential molecular target for the therapy of osteosarcoma.